Revitalisasi Pendidikan Melalui Kearifan Lokal: Pendekatan Etnografi Dalam Desain Kurikulum Di Iain Kerinci - Anggi Desviana Siregar; Ravico (Edification Journal : Pendidikan Agama Islam, 2026)
This research examines the integration of local wisdom into the curriculum at IAIN Kerinci, focusing on how ethnographic methods can create a culturally relevant and context-specific educational framework. As globalization rapidly advances, the need to incorporate local traditions, values, and cultural identities into education has become increasingly significant, especially in regions with rich cultural heritage like Kerinci. The study highlights the role of local wisdom, including ecological knowledge from the Kerinci Seblat National Park, local rituals, and historical religious practices, in shaping the curriculum. Findings reveal that embedding local wisdom enhances the curriculum's relevance and strengthens students' cultural identities and social sensitivity. Ethnographic methods, such as participatory observation and in-depth interviews, are key to uncovering and preserving neglected local cultural knowledge. The study also identifies challenges in implementing this curriculum, including resistance to change, limited resources for field research, and the need for a more robust institutional framework. The research concludes that integrating local wisdom through an ethnographic approach is crucial in developing an inclusive, contextually relevant curriculum that produces globally competent graduates, proud of their cultural heritage. This model offers valuable insights for other educational institutions in Indonesia and beyond.